2012
DOI: 10.1200/jco.2011.38.4818
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Stimulation Brain Mapping on Glioma Surgery Outcome: A Meta-Analysis

Abstract: Glioma resections using ISM are associated with fewer late severe neurologic deficits and more extensive resection, and they involve eloquent locations more frequently. This indicates that ISM should be universally implemented as standard of care for glioma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
482
4
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 885 publications
(552 citation statements)
references
References 33 publications
23
482
4
19
Order By: Relevance
“…18,21 To this end, functional mapping for guided resection performed using intraoperative direct stimulation was extensively demonstrated as representing a reliable and efficient technique to maximize the benefit/risk ratio of DLGG in eloquent areas. 4,6,9,24 Intrasurgical electrical mapping is particularly useful to identify the white matter tracts, because the brain's plastic potential is low at the subcortical level: any damage of the neural connectivity will generate permanent deficits. 7,28 In this study we used intraoperative axonal electrostimulation in awake patients to map the different pathways running in the SS.…”
Section: Surgical and Functional Considerationsmentioning
confidence: 99%
“…18,21 To this end, functional mapping for guided resection performed using intraoperative direct stimulation was extensively demonstrated as representing a reliable and efficient technique to maximize the benefit/risk ratio of DLGG in eloquent areas. 4,6,9,24 Intrasurgical electrical mapping is particularly useful to identify the white matter tracts, because the brain's plastic potential is low at the subcortical level: any damage of the neural connectivity will generate permanent deficits. 7,28 In this study we used intraoperative axonal electrostimulation in awake patients to map the different pathways running in the SS.…”
Section: Surgical and Functional Considerationsmentioning
confidence: 99%
“…Preoperative and intraoperative care should be taken to avoid surgical sequelae in the management of gliomas. 24,25 Accurate real-time positioning of intraoperative brain function is among the most important issues for neurosurgeons. In recent studies, R-fMRI was found to be well-correlated with the pre-and postoperative clinical condition of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Improving access to these resources may improve care, optimize resection, and reduce morbidity. 9 Our study does not establish which specific strategies or aspects of high-volume care are associated with improved outcomes. Additional study of clinical and practice barriers to selective referral, such as the distance from low-to high-volume hospitals, and the implications for patients remaining at low-volume hospitals is needed.…”
mentioning
confidence: 94%